Optimization of alpha-Fe2O3 Synthesis from Iron Sand via Extraction–Precipitation using Response Surface Methodology - Yudhistira, Nashrulfatih; Padmasari, Rahmita; Puspitawati, Ika Nawang; Muljani, Sri; Sani, Sani; Ramandani, Adityas Agung (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
The limited utilization of abundant iron sand in Indonesia highlights the need for efficient methods to produce value-added iron oxide materials. Among them, haematite (alpha-Fe2O3) has promising applications in energy, catalysis, and electronics, but its yield and quality depend strongly on process parameters, such as precipitation pH and calcination temperature. This study aims to optimize the synthesis of alpha-Fe2O3 from iron sand using the extraction–precipitation method by investigating the effects of precipitation pH and calcination temperature on the product yield. Iron sand was dissolved in hydrochloric acid, precipitated with potassium hydroxide at pH 5–9, and calcined at 400–800°C. Two-way ANOVA and response surface methodology (RSM) were applied to evaluate parameter effects and interactions. Results showed that both precipitation pH and calcination temperature significantly influenced yield, with optimum conditions at pH 7 and 600°C producing 18% alpha-Fe2O3. The quadratic RSM model accurately described the process and identified the optimum region. These findings demonstrate the potential of using local iron sand for the sustainable production of high-quality alpha-Fe2O3 for functional applications. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action